HTML for the World Wide Web, Fifth Edition, with XHTML and CSS - Castro, Elizabeth (Visual quickstart guide., 2002)
As both the Web and the browsers used to navigate it mature, work-arounds that compensate for the myriad factors that affect Web page appearance no longer cut it. Users expect Web pages to look beautiful regardless --and with the Fifth Edition of this popular Visual QuickStart Guide, you can make your Web pages comply. By following the generously illustrated, step-by-step instructions that are the hallmark of the Visual QuickStart series, you'll create beautiful code that works consistently across browser versions and platforms (including hand-held devices and cell phones) in no time. This updated edition includes a new section on foreign-language and multilingual Web sites as well as ample coverage on how the use of HTML is changing. What hasn't changed, however, is the book's popular format: Task-oriented, step-by-step instruction that builds on your growing knowledge. Info-packed appendixes, a comprehensive index, and plenty of screen shots and code examples make HTML for the World Wide Web, Fifth Edition, with XHTML and CSS: Visual QuickStart Guide a must-have reference. Whether you're just getting your feet wet (no prior HTML knowledge is required) or design Web sites for a living, you'll turn to this best-selling guide again and again for answers to all of your HTML-related questions.